Reflective practicum: innovative training strategies in Cantabria, Coimbra and Padua (Praxis Educativa, 2025)
We present research on the teaching practicum at the University of Cantabria, the University of Padua and the Polytechnic Institute of Coimbra. This article focuses on the reflective formative strategies deployed in these three institutions, analyzing in detail the implementation of the following: observation and interview, microteaching, peer mentoring and case study. Methodologically, it is framed in the qualitative paradigm and the data production was carried out from the information gathered in 14 semi-structured interviews with supervisors of the three institutions and from the analysis of official documents. The main results show the value of these strategies to train teachers who base their action on reflective movement and systematic research. We end the article by highlighting the conclusion that the most powerful reflective processes occur when several of these strategies act in synergy, favoring the reconstruction of the thinking and practice of future teachers.
Keywords: teacher training; teaching practice; teaching methods; comparative study; qualitative research